Phase analysis of gated myocardial perfusion single-photon emission computed tomography after coronary artery bypass graft surgery: reflection of late reverse remodeling in patients with patent grafts after coronary artery bypass graft surgery. Issue 11 (November 2016) - Park, Sohyun; Cheon, Gi Jeong; Paeng, Jin Chul; Won, Kyoung Sook; Kang, Keon Wook; Kim, Ki-Bong; Chung, June-Key; Lee, Dong Soo
Abstract : Objective: Phase analysis using gated myocardial perfusion single-photon emission computed tomography (GMPS) is a tool used to assess left ventricular (LV) dyssynchrony. We attempted to investigate the role of LV dyssynchrony assessed by GMPS using phase analysis for the late LV function after coronary artery bypass graft surgery (CABG) in patients with patent grafts. Methods: A total of 45 patients who received off-pump CABG with patent graft 1 year after CABG and preserved perfusion reserve were enrolled retrospectively. All patients underwent GMPS before and 3 months and 1 year after CABG. Using the Emory Cardiac Toolbox, both phase histogram bandwidth (PBW) and phase SD derived by phase analysis were used for the analysis, in addition to the conventional perfusion parameters. For the evaluation of LV function, transthoracic echocardiography was also performed. Results: All of the patients showed perfusion improvement (paired t -test, P <0.05) after CABG. Nonetheless, 30 of 45 patients showed LV dyssynchrony 3 months after CABG. One year after CABG, however, 25 out of 45 patients showed reverse remodeling. Among those patients with reverse remodeling, 19 patients had shown LV 3 months after CABG. Using stepwise logistic regression with forward selection, PBW 3 months after CABG could predict reverse remodeling 1 year after CABG (odds ratio 1.03, P <0.05). Using receiver operating characteristic analysis, PBW 3 months after CABG had the largest area under the curve to detect reverse remodeling 1 year after CABG with a cut-off value of 82 (sensitivity 0.95, specificity 0.56, P <0.001). Conclusion: Postoperative LV dyssynchrony assessed by GMPS using phase analysis may reflect late reverse remodeling and potential of further functional improvement in patients with patent grafts and preserved perfusion reserve after CABG. Abstract : Supplemental Digital Content is available in the text.